PEMIKIRAN POLITIK ISLAM NAJM AL DIN AL THUFI (Kajian Siyasah Syar’iyah) - Azzuhri Al Bajuri (Institut Agama Islam Negeri Batusangkar, 2019)
Najm al Din Al Thufi (Read. Najmuddin At-Thufi) was born in Baghdad Thuf Year 675 H/ 1277 M and died in 716 H in the city of Medina. He is known as the mujaddid mujtahid, al Thufi is considered to be a person who develops liberal thought in Islam because of his thoughts on the theory of mashlahah. This research is a library research using a normative approach and text analysis method. This study wanted to find the truth about Al Thufi liberal thinking in the field of Islamic political mashlahah, the result is that not true when al thufi regarded as liberal scholars, because mashlahah resting on precedence should only be reasonable if not contrary to the texts.